The Influence of Tax Understanding, Tax Rates and Tax Sanctions on Taxpayer Compliance in E-Commerce Actors in Luwuk City, Southeast Sulawesi - Muhammad Ilham Zulkarnain Sukiman Kau; Sahalina Ode Hasani; Irwan Moridu (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to analyze the effect of tax understanding, tax rates, and tax sanctions on taxpayer compliance on e-commerce actors in Luwuk City. The results show that all independent variables, namely tax understanding, tax rates, and tax sanctions, have a positive and significant effect on taxpayer compliance. Tax rates have the most dominant influence with a coefficient of 0.434, followed by tax sanctions of 0.317, and tax understanding of 0.176. This research model has an R-Square value of 0.551, which indicates that 55.1% of the variance in taxpayer compliance can be explained by these three variables. These findings indicate that reasonable tax rates, adequate tax education, and consistent application of sanctions can increase taxpayer compliance in the e-commerce sector.